Who gains from tariff escalation? - Basudeb Guha-Khasnobis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
With the help of a simple model of production and trade, we examine the differential impact of tariff escalation on skilled and unskilled wages in an economy. Our findings provide a lobbying-based explanation of the prevalence of tariff escalation in developed countries. It also predicts the possible response of a developing country and shows how similar lobbying activity in that country can slow the pace of liberalization of service sector trade.
Keywords: F01; F11; F13; 330; escalation; tariff; lobby; developing country; WTO; Zolltheorie; Protektionismus; Interessenpolitik; Entwicklungsländer